Evaluation of Deschampsia caespitosa /L./ Beauv. competition ability in mixtures with main turfgrass species - Jaroslav Martinek; Miluše Svobodová; Tereza Králíčková; Ivo Našinec (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2011)
Numbers of tillers and weight of aboveground dry mass were evaluated in a field experiment at the Plant breeding station Větrov of Oseva UNI Choceň a. s., Czech Republic (620 m a. s. l., average year temperature 6.9 ˚C, average year precipitation 642 mm) in mixtures of D. caespitosa cv. ‘Kometa’ with Poa pratensis L. cv. ‘Harmonie’ or with Lolium perenne L. cv. ‘Filip’ during three years of vegetation. The seeding rate was always 40 thous. viable seeds per m2. The proportion of D. caespitosa in the mixtures was 25%, 50% or 75% of the total number of seeds, a monoculture was established too. The sward was mown to 3 cm. D. caespitosa was not able to compete with L. perenne. The number of its tillers during the experiment ranged up to 3% of total number of tillers of the sward; the weight of aboveground DM was maximally 1.5% of the total aboveground phytomass. It established much better in the mixtures with P. pratensis. The total number of both components and the weight of aboveground dry mass was significantly influenced by the year (p-value < 0.000–0.009), by D. caespitosa proportion in the seed mixture (p-value = 0.001–0.003) and by the interaction of these factors (p-value = 0.000–0.056). It developed more rapidly in the first year in comparison with P. pratensis and reached 31–85% of total amount of tillers in positive correlation to its proportion in the seed mixture, later the competition capacity of P. pratensis increased and D. caespitosa tillers proportion in the sward was 11–39% in the third year. The trend of the weight of its aboveground dry mass was similar – 21–78% in the first year and 8–36% in the third year in a positive correlation with its proportion in the seed mixture. D. caespitosa and P. pratensis created bigger tillers in the later years.